2022
DOI: 10.1049/hve2.12258
|View full text |Cite
|
Sign up to set email alerts
|

Novel detection approach for thermal defects: Study on its feasibility and application to vehicle cables

Abstract: It is important to accurately assess the thermal defect state of equipment to ensure its safe operation. A novel thermal defect detection method called the square even-order derivative method is proposed. First, the derivative functions of temperature were constructed to investigate the main-side-peak characteristics of the derivative curve, and the mathematical expressions for the position, depth, intensity of the defects, and parameters of the derivative curve were deduced, which can be used to quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Starting from 1960 to 2020 a lot of researches have been done, at the international level and to some extent at the national level, to ascertain the influence of EMF on weld feature and to advocate the same to be used process parameter [ 81 , 82 , 83 ]. Following the 2000s, the majority of the research has aimed at exploring the effect of variable magnetic fields on the “droplet-transfer”, and the “spatter-control”.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from 1960 to 2020 a lot of researches have been done, at the international level and to some extent at the national level, to ascertain the influence of EMF on weld feature and to advocate the same to be used process parameter [ 81 , 82 , 83 ]. Following the 2000s, the majority of the research has aimed at exploring the effect of variable magnetic fields on the “droplet-transfer”, and the “spatter-control”.…”
Section: Resultsmentioning
confidence: 99%
“…The test was interrupted periodically and images of cracks were taken, after which the test was restarted again. It has been noticed that misalignment has a distinct effect on crack propagation rate [ 61 , 62 , 63 ]. It has been observed that the defect initiates from the edge and grows along the rolling direction and continues to spread with respect to time [ 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Note that, the optimization process based on the proposed scheme can be implemented on the network if there is smart grid technology in this network [38]. Te smart grid needs telecommunications [39][40][41][42] and smart devices [43][44][45][46]. Te deterministic model of the proposed scheme can be given as follows:…”
Section: A Deterministic Model Of the Proposed Schemementioning
confidence: 99%